A Realtime and Continuous Assessment of Cortisol in ISF Using Electrochemical Impedance Spectroscopy - Venugopal, Manju (2011)
This study describes the functioning of a novel sensor to measure cortisol concentration in the interstitial fluid (ISF) of a human subject. ISF is extracted by means of vacuum pressure from micropores created on the stratum corneum layer of the skin. The pores are produced by focusing a near infrared laser on a layer of black dye material attached to the skin. The pores are viable for approximately three days after skin poration. Cortisol measurements are based on electrochemical impedance (EIS) technique. Gold microelectrode arrays functionalized with Dithiobis (succinimidyl propionate) self-assembled monolayer (SAM) have been used to fabricate an ultrasensitive, disposable, electrochemical cortisol immunosensor. The biosensor was successfully used for in-vitro measurement of cortisol in ISF. Tests in a laboratory setup show that the sensor exhibits a linear response to cortisol concentrations in the range 1 pm to 100 nM. A small pilot clinical study showed that in-vitro immunosensor readings, when compared with commercial evaluation using enzyme-linked immunoassay (ELISA) method, correlated well with cortisol levels in saliva and ISF. Further, circadian rhythm could be established between the subject's ISF and the saliva samples collected over 24 hours time-period. Cortisol levels in ISF were found reliably higher than in saliva. This Research establishes the feasibility of using impedance based biosensor architecture for a disposable, wearable cortisol detector. The projected commercial in-vivo real-time cortisol sensor device, besides being minimally invasive, will allow continuous ISF harvesting and cortisol monitoring over 24 hours even when the subject is asleep. Forthcoming, this sensor could be interfaced to a wireless health monitoring system that could transfer sensor data over existing wide-area networks such as the internet and a cellular phone network to enable real-time remote monitoring of subjects.